The Exact Mean of the Two-Stage Least Squares Estimator of the Structural Parameters in an Equation Having Three Endogenous Variables - Ullah, Aman; Nagar, A. L. (Econometrica, 1974)
Aman Ullah, A. L. Nagar, The Exact Mean of the Two-Stage Least Squares Estimator of the Structural Parameters in an Equation Having Three Endogenous Variables, Econometrica, Vol. 42, No. 4 (Jul., 1974), pp. 749-758